Gut digestive enzymes and bacterial and fungal diversity of Apis mellifera adansonii (Hymenoptera: Apidae) from three ecological zones of Nigeria. Issue 1 (1st January 2021) - Bamidele, Julius A; Idowu, Adewumi B; Ademolu, Kehinde O; Osipitan, Adedoyin A; Atayese, Adijat O
ABSTRACT: Gut digestive enzymes and microbial diversity of worker honeybees, Apis mellifera adansoniiL. from rainforest, guinea savannah and derived savannah zones of Nigeria during the onset of rain, the wet season, and dry season was evaluated. The pour-plate method was used for microbial analysis while spectrophotometric method was used to determine activities of gut digestive enzymes. Gut activities of lipase and proteinase were not significantly different in the honeybees from the three ecological zones during the seasonal periods. However, amylase and α-glucosidase were significantly affected by seasonal periods and ecological zones. Bacterial count was higher on the body surface than in the gut of the honeybees. The lowest (gut and body surface) bacterial count was recorded during the dry season period. Fungal load counts on the body surface and gut were significantly different between the ecological zones during each of the seasonal periods. Bacterial species varied in the honeybees from the ecological zones and this was higher on the body surface than in their gut. Yeast isolate of the genus Candida was the only identified yeast on the body surface and in the gut of the honeybees. The gut of honeybees could selectively harbour microbes while performing digestive roles.